Why humans fight: the social dynamics of close-range violence - Malešević, Siniša (Cambridge University Press, 2022)
Malešević offers a novel sociological answer to the age-old question: 'Why do humans fight?'. Instead of focusing on the motivations of solitary individuals, he emphasises the centrality of the social and historical contexts that make fighting possible. He argues that fighting is not an individual attribute, but a social phenomenon shaped by one's relationships with other people. Drawing on recent scholarship across a variety of academic disciplines as well as his own interviews with the former combatants, Malešević shows that one's willingness to fight is a contextual phenomenon shaped by specific ideological and organisational logic. This book explores the role biology, psychology, economics, ideology, and coercion play in one's experience of fighting, emphasising the cultural and historical variability of combativeness. By drawing from numerous historical and contemporary examples from all over the world, Malešević demonstrates how social pugnacity is a relational and contextual phenomenon that possesses autonomous features.